Hypocrellin A-mediated photodynamic antibacterial activity against Cutibacterium acnes: An in vitro study - Muqiu Zhang; Xinyao Liu; Xin Ran; Runyan Gao; Jitong Sun; Kaiwen Zhuang; Zimeng You; Zhi Zhang; Yuping Ran (Photodiagnosis and Photodynamic Therapy)
Skin dysbiosis caused by Cutibacterium acnes contributes greatly to the complex pathogenesis of acne, and antimicrobial photodynamic therapy (PDT) has emerged as a promising treatment option for acne treatment. Hypocrellin, a photosensitizer extracted from a traditional Chinese medicinal fungus, has showed effective antimicrobial activity. This study aimed to evaluate the antibacterial ability of hypocrellin mediated PDT against Cutibacterium acnes. Using modified broth dilution method and morphological observation, the antibacterial effect was tested under a series of experimental conditions. The results showed that hypocrellin initiates type II photodynamic reactions by inducing amount of reactive oxygen species, particularly singlet oxygen. Within a certain concentration range, hypocrellin effectively maintained the antibacterial efficacy with minimal damage to keratinocyte cells. These results provide new insights into the use of PDT for acne treatment.